Stereoselective synthesis of a new methyl-substituted inositol derivative. Issue 38 (20th September 2019) - Kelebekli, Latif; Atlı, Ilknur
Abstract: The stereoselective synthesis of methyl-substituted inositol derivative is described. Diene diacetate which is a key compound was first prepared via three steps starting from 2-methyl- p -benzoquinone. Osmium-catalyzed regio- and stereoselective dihydroxylation of diene diacetate afforded cis -diol diasetate, which then produced tetra acetate via acetylation with Ac2 O-pyridine. Oxidation and acetylation of the other alkene moiety in the compound gave a hexaacetate compound stereoselectively. Finally, the acetate groups were removed by NH3 leading to formation of the desired new methyl-substituted inositol derivative having a muco -inositol-type stereochemical pattern in the six-membered ring. Spectroscopic methods were used for characterization of all synthesized compounds. Graphical abstract: Image 1 Highlights: Concise route to highly oxygenated small molecules was developed. The Osmium-catalyzed regioselectivity dihydroxylation of nonconjugated diene. The regio- and stereospecific first methyl-substituted inositol derivative was efficiently synthesized.